Analisis dan Perbaikan Usability Pada Aplikasi Ker Menggunakan Metode Usability Testing dan System Usability Scale (SUS) - Fatkhur Rosyad; Djoko Pramono; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Ker is a mobile-based application with an Android operating system that was inaugurated by the Malang city government in order to harmonize with the President of the Republic of Indonesia's regulations related to electronic-based government systems (SPBE) as well as towards smart city. The Ker application was made with the primary purpose of supporting and facilitating public services for people in the city of Malang. Based on the results of interviews and observations of 20 respondents, there are problems in the application of Ker related to usability problems. The problem is the existence of a function key and process that is not in accordance with what users expect from the application. Therefore, a study was conducted to determine the usability level of the Ker application. Usability testing is used to measure the level of usefulness of the aspects of effectiveness and efficiency, while the usability scale (SUS) questionnaire is used to determine the level of usefulness of the satisfaction aspect. The results showed that the level of usefulness from the aspect of effectiveness increased 5.13%, the aspect of efficiency 35.91%, and satisfaction by 16.42. If based on Sauro's SUS score (2018), the acceptable range that was previously in the